Relative Benefits of Aqueous Extract of Sorghum Residues with Herbicide on Weed Control and Yield of Wheat Varieties - Tonni, Nayema Haque; Sarker, Uttam Kumer; Ahmed, Md Towkir; Upama, Sinthia Ahmed; Rahman , Md Moshiur; Uddin, Md Romij (Journal of the Bangladesh Agricultural University, 2024)
Reducing herbicide use in agriculture is key for sustainability, addressing costs, environmental issues, and resistance problems. Using non-chemical methods like allelopathy in weed management offers a viable alternative. In this phenomenon, a field study was carried out at the Agronomy Field Laboratory (AFL) of Bangladesh Agricultural University (BAU), Mymensingh, from November 2021 to March 2022, to assess the phytotoxic effects of herbicides combined with aqueous extract of sorghum (AES) on weed management and yield of wheat. This study used three wheat varieties viz. BARI Gom (wheat)-32, BARI Gom-33, and BWMRI Gom-1 and six treatment levels such as, no weeding, recommended dose of herbicide (RDH), 90% RDH + AES (1:20 w/v), 80% RDH + AES (1:20), 70% RDH + AES (1:20), and 60% RDH + AES (1:20). The experiment followed a randomized complete block design (RCBD) with three replications. The RDH with AES and wheat variety significantly influenced weed population (WP) and dry weight (DW) of weeds. BARI Gom-32 produced the highest grain yield (GY) and other yield-contributing characteristics. The best results, including the highest numbers of tillers (NET) hill-1 (6.47), spike length (SL) (15.10 cm), number of spikelet spike-1 (NSS) (19.38), 1000-grain weight (TGW) (57.67g), GY (5.10 t ha-1), and straw yield (SY) (7.07 t ha-1) and harvest index (HI) (41.95%) were observed in plots treated with the RDH and the BARI Gom-32 variety, followed closely by those receiving 90% RDH + AES (1:20). The results demonstrate that varying concentrations of AES crop residue can effectively suppress weed growth and enhance wheat yield, suggesting that sorghum residues might be utilized to manage weeds effectively and sustainably while boosting wheat production. The study supports the potential of AES crop residue as an effective means to control weeds and significantly improve wheat yields. J Bangladesh Agril Univ 22(3): 326-334, 2024